The residential contextual façade techniques in improving indoor comfort for hot arid climate of Basra City: a review - Alhambosh, Ziadoon Ahmed; Abdul Ghafar, Maszura (Universiti Teknologi MARA, 2022)
Climate change is causing Iraq to experience extreme high temperature. This phenomenon has affected residents’ sense of comfort and incurred high energy consumption. The Residents’ thermal Comfort is still the main problem in hot and arid climate country such as Iraq particularly during summer resulting in expensive energy usage. This paper seeks to investigate how Basra City residents could achieve indoor comfort using contextual façade techniques. This study analysed factors that can affect residents’ indoor comfort and identified a balance between indoor comfort and energy usage. The desktop result suggested that contextual double skin façade and double-glazing typologies could improve indoor thermal comfort for residents. Using this contextual façade typology could potentially lead to energy saving. This study is limited to understanding the effect of contextual double skin and double glazing to residents in hot and arid climate. This study aids in reducing climate change and sustainable residents’ fiscal in energy consumption. Future development of this contextual façade typology could provide future guidelines and policies for façade treatment in hot and arid countries.